Overeducation and Ethnic Minorities in Britain - Harminder Battu; Peter J. Sloane (Institute for the Study of Labor (IZA), 2002)
This study examines the utilisation of education across ethnic minorities in the UK. In particular, we examine the incidence of mismatch between educational qualifications and occupational attainment, the determinants of any mismatch and the consequences for earnings and other labour market outcomes. Using a modal measure of required education across sixty occupations we find that different ethnic groups have varying levels of overeducation with the highest incidence being amongst the Indian and Africa-Asian groups. When we introduce controls we find that the African-Asians are more likely to be both over and under-educated relative to Indians (the omitted group), but this is reversed for those born in the UK. Foreign qualifications increase the likelihood of over-education for Pakistanis and Bangladeshis but reduce it for African-Asians. Language fluency increases the likelihood of mismatch. The results from our earnings regressions support previous work in relation to the returns to over, required and under-education, though with differences between native and immigrant non-whites.
Keywords: I2; J3; J7; 330; ethnic minorities; educational qualifications; mismatch; earnings; Qualifikation; Überqualifikation; Ethnische Gruppe; Lohn; Schätzung; Großbritannien